ADVANTAGES OF VIRTUAL TOURS IN RFL TRAINING - Babayeva Anjella Axatovna (Web of Journals Publishing, 2025)
The article examines the advantages of virtual excursions in teaching Russian as a foreign language (RFL). Virtual excursions allow students to immerse themselves in the language environment, visualize the material being studied, increase motivation a nd develop communication skills. They provide accessibility and flexibility to the learning process, making it more fun and effective. Aspects such as interactivity, cost-effectiveness, and the ability to use technology to enhance the educational experience are considered.
Keywords: Visualization, communication skills, interactivity, language environment, interactive learning.